Digital Transformation of Education and Challenges of the 21st Century - A. D. Korol; Yu. I. Vorotnitsky (Высшее образование в России)
The purpose of the article is to analyze the topical problems of the digital transformation of education as a process of changing its goals, meanings, content and technologies and to find ways to solve them. The authors emphasize the primacy of pedagogical innovations and the auxiliary role of information technologies providing the technological basis for the creation and application of new pedagogical practices. The analysis of changes in the educational process in the context of the expansion of the digital educational space and the possibilities of distance technologies leads to the conclusion that the use of the traditional one-way monologue transmission of knowledge on modern digital platforms is ineffective. The paper proposes the methodology based on the self-study underpinned by the mankind achievements, the creation of student’s own system of knowledge, when he gives his meaning to the world and changes him/herself, developing his/her creative abilities. This methodology has been proven to work and tested in practice. The article presents an experience of the Belarusian State University (hereinafter – BSU) in the development and implementation of the concept of creative education, the deployment of a large-scale program for the introduction of distance technologies. The practical steps for the implementation of this program are described, such as the development of a new educational and methodological literature, the creation of an interuniversity portal “Methodology, content, and practice of creative education”, the implementation of the full-time distance training program “Technologies of heuristic education in higher education: teaching methods through discovery” and the project “Online Learning Workshop”. The main quantitative indicators of the effectiveness of the digital transformation of the educational process at BSU are analyzed. The authors describe the information infrastructure of BSU, which ensures the implementation of innovative pedagogical technologies: telecommunications infrastructure and a “cloud” data center, an educational process management system integrated with corporate systems and services, its own video conferencing system, an integrated automated information system developed by the university.